Genetic diversity analysis based on morphological characters in mulberry (Morus spp.) (Journal of Bio-Science, 2019)
Mulberry genetic resource is increasingly being recognized as one of the basic key component for sustainable silk production under changing climatic condition. In this investigation, analysis of multivariate was done to assess the diversity in 20 mulberry genotypes (includes indigenous and exotic) for leaf yield and its growth attributes. The analysis of variance (ANOVA) showed the presence of significant variation among genotypes for the parameters measured. Wide range and variance among the genotypes indicated the presence of variability for the traits on which selection can be practiced. For cluster analysis classified 20 genotypes into four divergent groups and greater genetic distance was detected among the members of cluster I and II and cluster II and III. The members of these divergent clusters may be combined in future breeding programmes to obtain genotypes with combined leaf yield and more branches per plant. The results showed that the germplasm having a wide genetic diversity thus the genotypes viz., BSRM64, BSRM66, BSRM63, BSRM65, BSRM45 and BSRM56 can serve as a promising donors for improving the leaf productivity of mulberry.J. bio-sci. 28: 111-119, 2020